2011
DOI: 10.2166/wh.2010.190
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of electropositive filtration for recovering norovirus in water

Abstract: The virus adsorption-elution (VIRADEL) technique has been widely used in the recovery of various enteric viruses in water, and an electropositive filter such as 1 MDS has been commonly applied.However, effective methods of monitoring waterborne norovirus (NoV) have not yet been well characterized and optimized. Hence, in this study, the VIRADEL technique was evaluated and optimized for effectively detecting NoV in water by two commonly used electropositive filters (1MDS and NanoCeram filter). Various elution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 38 publications
4
15
0
Order By: Relevance
“…The advantage to the use of murine norovirus is that high titers can be obtained via cell culture (24). In addition, our mean recovery rate of 29% for murine norovirus in groundwater is similar to that found previously for human noroviruses by Lambertini and colleagues, at 29% (21), and slightly higher than the 18% recovery that was demonstrated previously by Lee and colleagues (34). In addition, the studies by both Karim et al and Lee and colleagues demonstrated the effectiveness of the NanoCeram filter in recovering human noroviruses from spiked water samples (17,34).…”
Section: Discussionsupporting
confidence: 90%
“…The advantage to the use of murine norovirus is that high titers can be obtained via cell culture (24). In addition, our mean recovery rate of 29% for murine norovirus in groundwater is similar to that found previously for human noroviruses by Lambertini and colleagues, at 29% (21), and slightly higher than the 18% recovery that was demonstrated previously by Lee and colleagues (34). In addition, the studies by both Karim et al and Lee and colleagues demonstrated the effectiveness of the NanoCeram filter in recovering human noroviruses from spiked water samples (17,34).…”
Section: Discussionsupporting
confidence: 90%
“…Poliovirus recoveries from ground and reagent grade waters and murine norovirus recoveries from groundwater met the EPA Method 1615 performance acceptance criteria (Table 11) and are similar to those reported by others 33,37,38 . Murine norovirus recoveries from LFB samples were much lower than those of poliovirus and would not have met the poliovirus-specific acceptance criteria.…”
Section: Discussionsupporting
confidence: 80%
“…Similar to the results herein, Karim and colleagues reported a recovery for norovirus GI.1 of 4% from tap water 39 . Lee et al 37 reported mean recoveries for murine norovirus and human norovirus GII.4 of 18% and 26% from distilled water using disc filters, respectively. Using similar conditions to Lee and colleagues, Kim and Ko observed recoveries of 46% and 43% for these viruses, respectively 38 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that different secondary concentration techniques can affect virus recoveries 6,13,19,20 . Celite concentration has been shown to recover similar levels of virus to that of other secondary concentration methods 8,14 from a variety of matrices, while using quicker and simpler sample processing procedures.…”
Section: Discussionmentioning
confidence: 99%